When Cloud became a cloud - Hodgson, Rob (Rise x Penguin Workshop, an imprint of Penguin Random House, 2021)
"Meet Cloud! Follow along as she moves, transforms, precipitates, and more in this charming and humorous portrayal of the water cycle. From drizzle to snow to a thunderstorm party, Cloud's journey is documented through short, engaging chapters that capture the excitement and humor of weather in its many forms."--Provided by publisher.